2006
DOI: 10.1111/j.1366-9516.2006.00241.x
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of resource selection functions across spatial scales

Abstract: International audienceResource selection functions (RSFs) can be used to map suitable habitat of a species based on predicted probability of use. The spatial scale may affect accuracy of such predictions. To provide guidance as to which spatial extent or grain is appropriate and most accurate for animals, we used the concept of hierarchical selection orders to dictate extent and grain. We conducted a meta-analysis from 123 RSF studies of 886 species to identify differences in prediction success that might be e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
154
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(155 citation statements)
references
References 77 publications
1
154
0
Order By: Relevance
“…For example, modeling methods have been developed that use presenceonly data [11]; the impact of limited sample size in modeling have been studied [5,12]; and solutions have been proposed for the problem of incorrectly located species records [13], uneven sampling effort [14][15][16], spatial autocorrelation [17][18][19][20], and scales [21,22]. However, not all deficiencies in species data sets have been fully studied.…”
Section: Introductionmentioning
confidence: 99%
“…For example, modeling methods have been developed that use presenceonly data [11]; the impact of limited sample size in modeling have been studied [5,12]; and solutions have been proposed for the problem of incorrectly located species records [13], uneven sampling effort [14][15][16], spatial autocorrelation [17][18][19][20], and scales [21,22]. However, not all deficiencies in species data sets have been fully studied.…”
Section: Introductionmentioning
confidence: 99%
“…More generally, Schneider et al (1987) found that mobile species often show decoupling from the environment at finer scales, and habitat association at coarser scales, compared to finer-scale coupling with habitat by sessile species. Meyer & Thuiller (2006) reported that the majority of species respond to habitat characteristics at more than one scale at the same time. Despite that, a response measured at one particular scale cannot always be used to predict habitat use at another scale (VanderWerf 1993, Apps et al 2001.…”
Section: Scale In Ecologymentioning
confidence: 99%
“…Many SDMs provide general predictions of distribution based on coarse-grain metrics often over broad spatial extents (e.g., patch size) that can reflect coarse patterns of habitat use and provide predictions for broad spatial extents for a variety of conservation and management goals (Betts et al 2007, Collier et al 2012. However, habitat use and resulting distributions can be driven by habitat characteristics assessed by organisms at multiple spatial extents and grains, including fine-grained conditions across relatively small spatial extents (Orians and Wittenberger 1991, Meyer and Thuiller 2006, Chalfoun and Martin 2007. Ecological research commonly investigates the role of fine-grained vegetation metrics over small spatial extents when investigating responses such as territory selection or nest site selection (Misenhelter and Rotenberry 2000).…”
Section: Introductionmentioning
confidence: 99%